Frontispiece: Chemical Functionalization of Polysaccharides—Towards Biocompatible Hydrogels for Biomedical Applications. Issue 6 (26th January 2018) - Kirschning, Andreas; Dibbert, Nick; Dräger, Gerald
Abstract : Functionalized polysaccharides have emerged as versatile scaffold materials for the formation of hydrogels used in biomedical applications and tissue engineering. Important to such polysaccharides‐based materials are recent developments in synthetic chemistry to specifically functionalizing polysaccharides such as hyaluronic acid, alginate, dextran or pullulan. For more details, see the Minireview by A. Kirschning, G. Dräger and N. Dibbert onpage 1231 ff.